Analysis of training programs related to quality management system: the Spanish case. Issue 2 (6th February 2017) - Petnji Yaya, Luc Honore; Marimon, Frederic; Llach, Josep; Bernardo, Merce; Casadesus, Marti
Abstract : Purpose: The purpose of this paper is to identifying, discussing and analyzing the existing education and training programs related to quality management system (QMS) in Spain. Design/methodology/approach: Exhaustive search of the education system database was used to map the multifaceted of Spanish education system and professional training in addition to their relationships with the labor market. Thereafter, a thorough scan of the existing training related to management system standards was used to classify them into different subgroups as well as identifying possible education and the professional trainings related to QMS. Findings: The overall results showed that general education in Spain and in particular related to QMS can be classified into four different groups including: official university, unofficial university, official non-university and unofficial non-university. Moreover, this study observed that the general concern about the employment and earnings in Spain has led the local, autonomous communities and national government to launch specific measures designed to both continue to increase the quality of the workforce with the QMS backgrounds and to ease the difficulties encountered when entering the labor market. Originality/value: This study is the first to analyze and map the multifaceted character of Spanish education system and professional training related to QMS. The findings of this study may be useful for organizations trying to evaluate their QMS efforts, thus, engage their people in order to face the competitive challenges that lie ahead.